2016
DOI: 10.1139/cjps-2014-0265
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the 1-aminocyclopropane-1-carboxylate deaminase gene of the biocontrol fungus Trichoderma asperellum ACCC30536

Abstract: 1-aminocyclopropane-1-carboxylate (ACC) deaminase (ACCD) cleaves ACC, the immediate precursor of the ethylene, decreasing the level of ethylene and inhibition of plant growth resulted by environmental stresses. Here, TaACCD was cloned from the biocontrol agent Trichoderma asperellum ACCC30536. Its open reading frame was 1047 bp long encoding a 37 kD protein of 348 aa, and a pI of 5.77. Phylogenetic analysis demonstrated this protein to be closely related to ACCD from T. asperellum T203 (ACX94231). Transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Thereby, it induces the growth of plant and root under biotic and abiotic stress (Glick, 2014). For the first time, Zhang et al (2016) analyzed the ACC deaminase gene of the biocontrol fungus T. asperellum ACCC30536. In this present investigation, the expression of ACC deaminase was up-regulated in co-cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, it induces the growth of plant and root under biotic and abiotic stress (Glick, 2014). For the first time, Zhang et al (2016) analyzed the ACC deaminase gene of the biocontrol fungus T. asperellum ACCC30536. In this present investigation, the expression of ACC deaminase was up-regulated in co-cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the current finding, it has been reported that soil fungal isolates from metal-polluted soil revealed a different HM tolerance profile. Many metal-tolerant fungi, such as Trichoderma sp., Aspergillus welwitschiae, Alternaria sp., Chaetomium globosum, Epicoccum nigrum, Polygonum acuminatum, and Aeschynomene fluminensis, Trichoderma brevicompactum QYCD-6 etc., have been described for their vital functions in HM remediation and agricultural crop improvement. Interestingly, global study and research are being conducted to determine why microbial populations vary so greatly in their capacity to withstand dangerous contaminants like HMs.…”
Section: Resultsmentioning
confidence: 99%